Towards Reliable Rule Mining about Code Smells: The McPython Approach - Ziobrowski, Maciej; Ochodek, Miroslaw; Nawrocki, Jerzy; Walter, Bartosz (2023 18th Conference on Computer Science and Intelligence Systems (FedCSIS), 2023)
CODE smell is a risky pattern in code that can lead, in the future, to problems with code maintenance. One of the approaches to identifying smells in the code is metric-based smell detection. A classic example is the God Class smell which can be detected by using three metrics (see, e.g., [1]-[3]): * Weighted Method Count (WMC - sum of McCabe's complexity of all methods in the analysed class), * Tight Class Cohesion (TCC - relative number of directly connected methods within the analysed class), and * Access to Foreign Data (ATFD - number of classes containing attributes referenced by the analysed class directly or via get/set methods).